2016
DOI: 10.3201/eid2207.151319
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality Rates Associated withStaphylococcus aureusand Influenza Co-infection, Maryland and Iowa, USA1

Abstract: We retrospectively analyzed data for 195 respiratory infection patients who had positive Staphyloccocus aureus cultures and who were hospitalized in 2 hospitals in Iowa and Maryland, USA, during 2003–2009. Odds for death for patients who also had influenza-positive test results were >4 times higher than for those who had negative influenza test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…A report of the 2009-2010 influenza pandemic among critically ill children revealed that nearly 5% of the patients had bacteremia within 72 h and Staphylococcus aureus was the most frequently isolated bacterium, which contributed to the death rate in the current pandemic [33]. In a study of 32 influenza-positive patients (including pediatric and adult patients), poor outcomes were found among patients who were coinfected with influenza viruses and Staphylococcus aureus [34]. Although we were unable to conclude whether or not initiating timely additional antimicrobial treatment in critically ill influenza patients led to better clinical outcomes, our findings and previous reports underscore that Staphylococcus aureus remains the most important cause of bacterial coinfection in pediatric and adult influenza patients.…”
Section: Discussionmentioning
confidence: 99%
“…A report of the 2009-2010 influenza pandemic among critically ill children revealed that nearly 5% of the patients had bacteremia within 72 h and Staphylococcus aureus was the most frequently isolated bacterium, which contributed to the death rate in the current pandemic [33]. In a study of 32 influenza-positive patients (including pediatric and adult patients), poor outcomes were found among patients who were coinfected with influenza viruses and Staphylococcus aureus [34]. Although we were unable to conclude whether or not initiating timely additional antimicrobial treatment in critically ill influenza patients led to better clinical outcomes, our findings and previous reports underscore that Staphylococcus aureus remains the most important cause of bacterial coinfection in pediatric and adult influenza patients.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza viruses are responsible for an average of 400,000 deaths per year globally (Simonsen et al, 1997 ; Bakaletz, 2004 ; King et al, 2017 ; Tansey, 2017 ). During previous influenza pandemics (H1N1, 1918; H2N2, 1957; H3N2, 1968; H1N1, 2009) and seasonal epidemics, many influenza-related deaths actually occurred due to bacterial co-infections (Guarner et al, 2006 ; Taubenberger and Morens, 2008 ; Weiser, 2010 ; Klein et al, 2016 ; McDanel et al, 2016 ; Shah et al, 2016 ). Since the 1950s, researchers have increasingly focused on concomitant infections with influenza viruses and a range of bacterial agents (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Superinfections caused by bacteria during respiratory viral infections found associated with significant cause of death 23 . In a previous study an increased mortality was observed in coinfection of staphylococcus aureus with Influenza in hospitals of Iowa and Maryland, USA during 2003 -2009 24 .…”
Section: Fig 2: the Gel Image Showing Polymerase Chain Reaction Amplmentioning
confidence: 89%